Inventory Management for an Import Company of Power Transmission Spare Parts for Heavy Machinery - Núñez-Oviedo, Mateo (2024)
The aim of this study was to analyses the inventory management of a company that imports power transmission spare parts. The study was of the applied type, with a non-experimental design, descriptive scope, and quantitative approach. A company importing its products from China was taken as a case study. Deterministic and stochastic scenarios were evaluated in comparison with the company’s current scenario and methods related to each scenario were applied, also considering the behavior of demand, and analyzing the models with forecasts of these. It was concluded that the stochastic method, specifically the (S, T) model, has proved to be more profitable compared to the current scenario and the deterministic one, mainly due to the reduction of shortages and the homogeneity in the behavior of the inventory.